Sprachgebrauch vs. Spracheinstellung im Tschechischen Empirische und soziolinguistische Untersuchung in Westboehmen und Prag - Bayer, Lenka (Slavistische Beitraege, 2003)
The first level of the present work is methodologically concerned with the planned Prague corpus of spoken Czech. Spoken texts are recorded, fixed in writing and arranged according to linguistic and sociological criteria and evaluated. The goal is to sketch the current situation in spoken Czech from the recordings and thus to contribute to the above-mentioned discussion about the relationship between ST vs. ST. GT. The second level of this study complements the evaluation of the linguistic material. Sociological data collected by questionnaires and data provided by the same speakers in the field of ST: 1) knowledge (cognition); 2) degree of positive evaluation; 3) but above all the readiness (Konation) of the speaker for use of the ST examined. The attitude of the Czechs to their standard language, secondary to their Koine, is here in the foreground. This publication makes an important contribution to the intensified discussions about Standard Czech and Common Czech (Bohemian Koiné) since the political change in the Czech Republic.